2014
DOI: 10.5665/sleep.3558
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Versus Pramipexole: Effects on Sleep Disturbance in Restless Legs Syndrome

Abstract: ClinicalTrials.gov identifier, NCT00991276; http://clinicaltrials.gov/show/NCT00991276.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 38 publications
0
62
0
1
Order By: Relevance
“…Because results of this Class I study were not statistically significant and CIs included both potentially clinically important and unimportant effects, there is insufficient evidence to support or refute the effect of gabapentin enacarbil on the PLMI. It is likely that gabapentin enacarbil improves RLS-specific QoL (1 Class I study 37 ) and mood (1 Class I study 36 24,25,40 ; there is insufficient evidence to support or refute doses of 50-100 mg/d because analyses did not reach statistical significance but CIs 1 of which had insufficient precision at many doses). Pregabalin 300 mg possibly improves RLS-related QoL (1 Class II study 25 ; 1 Class I study 39 reported no difference but did not provide data to assess).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Because results of this Class I study were not statistically significant and CIs included both potentially clinically important and unimportant effects, there is insufficient evidence to support or refute the effect of gabapentin enacarbil on the PLMI. It is likely that gabapentin enacarbil improves RLS-specific QoL (1 Class I study 37 ) and mood (1 Class I study 36 24,25,40 ; there is insufficient evidence to support or refute doses of 50-100 mg/d because analyses did not reach statistical significance but CIs 1 of which had insufficient precision at many doses). Pregabalin 300 mg possibly improves RLS-related QoL (1 Class II study 25 ; 1 Class I study 39 reported no difference but did not provide data to assess).…”
mentioning
confidence: 99%
“…There is insufficient evidence to support or refute the superiority of pregabalin over pramipexole for treating IRLS symptoms (metaanalysis of 2 Class II studies 24,25 where the mean difference point estimate is not compared with pramipexole). Pregabalin likely improves subjective sleep outcomes more than pramipexole (2 Class II studies 24,25 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Integration of newly reported indices into HSMD have the potential to provide valuable clinical information on the various PLM phenotypes, [7][8][9][10] genotypes [11,12] and efficacy of pharmacological interventions [13].…”
Section: Why Are Hsmd the Tools To Assess Plms?mentioning
confidence: 99%